Photo-Anthropometric Study of Breadth of Eye and Intercanthal Distance Among Tribal Garo and Non-tribal Adult Bangladeshi Females of Mymensingh Zone - Tania, Israt Jahan; Ara, Shamim; Naushaba, Humaira; Paul, Uttam Kumar; Akhter, Mahbuba (International Journal of Human and Health Sciences (IJHHS), 2022)
Background: Anthropometry provides quantitative data in identifying people having different physical characteristics in diagnosing people having craniofacial abnormality and to compare between patient and normal population. The eye is a person’s most defining feature because the shape of the eye differs from race to race, tribe to tribe and from one environment to another. Objective: To see craniofacial anthropometric differences between tribal (Garo) and non-tribal Bangladeshi females. Materials & Methods: This cross sectional, analytical type of study was conducted in the Department of Anatomy, Sir Salimullah Medical College, Dhaka, from January to December of 2015. The study subjects consist of two hundred adult Bangladeshi females of Mymensingh Zone – 100 were tribal (Garo) females and 100 were non-tribal females. Results: The mean breadth of eye from ‘distance between outer and inner canthus of right and left eye ’was higher in non- tribal female than tribal (Garo) female and was statistically significant (P<0.001) and intercanthal breadth from ‘distance between inner canthus of right and left eye’ was higher in tribal female than non-tribal female and was statistically significant (P<0.05). Conclusion: The breadth of the eye was greater in non- tribal female and intercanthal breadth was greater in tribal females. International Journal of Human and Health Sciences Vol. 06 No. 01 January’22 Page: 104-107